EFFECTS OF DIFFERENT WATERING FREQUENCY GROWTH AND BIOMASS PRODUCT OF STEVIA PLANT (STEVIA REBAUDIANA BERTONI) USING FERTIGATION WATERING SYSTEM - Sativa, Ryza
Sugar is one of the daily intake needs of humans that gives a sweet taste to food and drinks. In general, this sugar is made from sugar cane which has high calories that can trigger diabetes when consumed in excess. One alternative to cane sugar is stevia sugar with close to zero calories. This stevia sugar has not been widely produced because the wet biomass itself has not met the market needs. The stevia plant is a water-sensitive plant where less or more quantity can affect the quality and quantity of its production. One solution that can be applied is the use of drip fertigation technology. This technology can regulate the amount of water application and the quantity of water application in one time. Based on this, research was conducted on the effect of volume and frequency of water application on the growth of stevia plants, the effect of volume and frequency of water application on the biomass yield of stevia plants, the best volume and frequency treatment on the growth of stevia plants, and the best volume and frequency treatment on the biomass yield of stevia plants. The research was conducted using a completely randomized design (CRD) with 8 replications of 4 plants per replication and treatments in the form of P1 = Frequency of irrigation 2 times a day with a total irrigation volume per day of 240 mL (120 mL per irrigation), P2 = Frequency of irrigation 3 times a day with a total irrigation volume per day of 360 mL (120 mL per irrigation), and P3 = Frequency of irrigation 4 times a day with a total irrigation volume per day of 480 mL (120 mL per irrigation). Based on the research, it was found that (1) differences in the volume and frequency of watering per day had an effect on the growth and yield of stevia plants. The frequency and volume treatments produce a6 significant effect on plant growth, but the parameters do not produce a significant effect on the yield parameters and (2) the best treatment is the P3 treatment (480 mL irrigation volume per day with a frequency of administration 3 times per day) with significant values in the parameters of plant height, number of branches, crown diameter, and root length and not significant in the parameters of wet weight of harvest, dry weight of harvest, whole plant weight, root weight, and crown weight.